If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -1 + y + 35 = 7 + 7y + 33 + -5y Reorder the terms: -1 + 35 + 3y + y = 7 + 7y + 33 + -5y Combine like terms: -1 + 35 = 34 34 + 3y + y = 7 + 7y + 33 + -5y Combine like terms: 3y + y = 4y 34 + 4y = 7 + 7y + 33 + -5y Reorder the terms: 34 + 4y = 7 + 33 + 7y + -5y Combine like terms: 7 + 33 = 40 34 + 4y = 40 + 7y + -5y Combine like terms: 7y + -5y = 2y 34 + 4y = 40 + 2y Solving 34 + 4y = 40 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 34 + 4y + -2y = 40 + 2y + -2y Combine like terms: 4y + -2y = 2y 34 + 2y = 40 + 2y + -2y Combine like terms: 2y + -2y = 0 34 + 2y = 40 + 0 34 + 2y = 40 Add '-34' to each side of the equation. 34 + -34 + 2y = 40 + -34 Combine like terms: 34 + -34 = 0 0 + 2y = 40 + -34 2y = 40 + -34 Combine like terms: 40 + -34 = 6 2y = 6 Divide each side by '2'. y = 3 Simplifying y = 3
| 8w+6w=82 | | (x-4)2=(x-2) | | 4-t=2xa+21 | | 15x=498 | | x^2+27x-468=0 | | y^2-16y^2=0 | | 6x-5+8y=-22 | | -5*-3=15-7c | | x-9x=-4*6 | | (8+w)(2w+9)=0 | | 6-2n=1-8n+5 | | 3x+5-6x=10+2x | | -2(z+3)-z=-z-5(z+2) | | x^6+3x^3-4= | | 17x=8x+8 | | -2*-4=o | | 4x-2+2x-5=77 | | 4(5z-1)-5(2+9)=2(z+1) | | 2*-4=o | | -2*-4=ourfgn | | sin(7x)=cos(7x) | | (2d^2-9d)-(-4d^2+20d+17)= | | 2x+(18-x)=11 | | 6(-2)=r+5r | | P(x)=(60x-0.3x^2)-(5x+13) | | 3x+1/3=3x-1/2 | | ln(16x)= | | 5x+14=2+7x | | -1(-1)=z | | 2cos(3x-1)=0 | | 32=2(x+4.5) | | (c^2-9c-5)-(-c^2-8c-10)= |